The influence of financial technology, personality traits, and financial literacy on financial attitude, personal saving orientation, and family financial planning, moderated by financial quotient among naval families. “A study of Hera naval base, Timor-Leste” - Loe, Duarte Borges; Ratnawati, Tri; Pristiana, Ulfi (Edelweiss Applied Science and Technology, 2024)
Family financial planning is becoming more and more crucial, particularly in military environments where certain challenges can affect financial habits. The study looks at moderating role of financial quotient on the correlation between financial technology, personality traits, and financial literacy and family financial planning of naval families at Naval Base Hera. Although certain factors of financial behaviour have been studied before, how these factors are interrelated within military families is still unclear. This research seeks to fill this gap by employing a causal explanatory research method that analyze sources from 248 married Navy personnel through using a structural equation modeling (SEM) approach with Smart PLS. The findings paint a picture that where Fintech influences the financial behaviours of individuals and families, such traits for personality and financial literacy inform their attitudes and ever financial planning. Posted here, it is revealed that financial quotients have a moderate influence on the results of family financial planning. Thus, this research highlights the need to design and implement financial education interventions that incorporate technology support and improve the financial literacy of naval officers with policy implication for the authorities as well as other denominations in the teaching of financial education. This research fills this gap making a positive contribution in the understanding of financial management in military environment hence contributing to the informing of policies that foster better financial stability and well-being of families of soldiers serving in the navy.